Factors affecting bank customers usage of electronic banking in Ethiopia: Application of structural equation modeling (SEM) - Beza Muche Teka (Cogent Economics & Finance, 2020)
Electronic banking services have not been widely used by most bank customers in Ethiopia; most bank customers continue to conduct most of their banking transactions using traditional methods. Therefore, the main objective of this study is to identify factors that affect customers' usage of electronic banking services. The type of research applied in this study is explanatory in nature. A research model was developed by integrating the constructs of Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB). A total of 420 actual users of e-banking services were used as a sample. A well-structured questionnaire was used to collect the relevant information. The data analyzed using Structural Equation Modeling revealed that perceived usefulness, perceived ease of use, attitude towards e-banking, perceived behavioral control, subjective norms, behavioral intention, awareness as well as the availability of internet/network connection have a significant positive impact on users e-banking usage practice. However, perceived risk has a significant negative impact. These findings suggest that banks in Ethiopia should create awareness to their customers with regard to the usage and benefits of e-banking service delivery channels.
Keywords: 330; E-banking; technology acceptance model (TAM); theory of planned behavior (TPB) and structural equation modeling (SEM)